Spectrum of uropathogens and their antibiotic sensitivity pattern in diabetes mellitus patients at a tertiary care hospital in Odisha, India - Murmu, Malati; K. P., Karun Mahesh; Meher, Rajesh Kumar; Pradhan, Butungeshwar; Kar, Ayaskanta; Naik, Manoranjan (International Journal of Research in Medical Sciences, 2018)
Background: Diabetes Mellitus is the most common endocrine disorder involving almost all systems of body. Untreated or poorly treated Diabetics are susceptible to develop a series of complications responsible for raised morbidity and mortality. Diabetes Mellitus has a number of long term effects on the Genitourinary system. Urinary tract infections have long been recognised as a significant problem in patients with Diabetes Mellitus. Methods: Prospective observational study. Diabetic patients with culture positive UTI were included. Gestational diabetes, Immunocompromised patients and patients with congenital renal anatomical abnormalities were excluded. Results: Authors included 211 numbers of culture positive UTI among diabetic patients. Out of which, 65 were male and 146 were female. Maximum number of patients belong to 56-65 years age group. Escherichia coli was the predominant organism isolated. Gram positive organisms showed 100% sensitivity to Vancomycin and Linezolid. Gram negative organisms showed 100% sensitivity to Polymyxin B. Conclusions: Genitourinary tract infection is not an infrequent complication seen in diabetes patients. Most common causative organism and their antibiotic sensitivity pattern should be done in tertiary care hospital for a better antibiotic policy.